2013
DOI: 10.1021/nn4018872
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency MoS2 Nanomechanical Resonators

Abstract: Molybdenum disulfide (MoS2), a layered semiconducting material in transition metal dichalcogenides (TMDCs), as thin as a monolayer (consisting of a hexagonal plane of Mo atoms covalently bonded and sandwiched between two planes of S atoms, in a trigonal prismatic structure), has demonstrated unique properties and strong promises for emerging two-dimensional (2D) nanodevices. Here we report on the demonstration of movable and vibrating MoS2 nanodevices, where MoS2 diaphragms as thin as 6 nm (a stack of 9 monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
287
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(295 citation statements)
references
References 36 publications
5
287
1
2
Order By: Relevance
“…For SLMoS 2 , two recent experiments demonstrated the nanomechanical resonant behavior in SLMoS 2 [101] and few-layer MoS 2 [102]. Castellanos-Gomez et al found that the figure of merit, i.e., the frequency-Qfactor product, is f 0 × Q ≈ 2 × 10 9 Hz for SLMoS 2 [101].…”
Section: Nanomechanical Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SLMoS 2 , two recent experiments demonstrated the nanomechanical resonant behavior in SLMoS 2 [101] and few-layer MoS 2 [102]. Castellanos-Gomez et al found that the figure of merit, i.e., the frequency-Qfactor product, is f 0 × Q ≈ 2 × 10 9 Hz for SLMoS 2 [101].…”
Section: Nanomechanical Resonatorsmentioning
confidence: 99%
“…Castellanos-Gomez et al found that the figure of merit, i.e., the frequency-Qfactor product, is f 0 × Q ≈ 2 × 10 9 Hz for SLMoS 2 [101]. Lee et al found that few-layer MoS 2 resonators exhibit a high figure of merit of f 0 ×Q ≈ 2×10 10 Hz [102]. The high Q-factor of SLMoS 2 could be attributed to the energy band gap in the phonon dispersion of SLMoS 2 , which protects the resonant oscillations from being scattered by thermal vibrations [47].…”
Section: Nanomechanical Resonatorsmentioning
confidence: 99%
“…The SiCon-SiO 2 technology creates novel centre-anchored circular SiC microdisks featuring a uniform gap defined by the SiO 2 thickness, which is ideal for precision optical interrogation. We have developed an ultrasensitive scanning laser interferometry scheme featuring an B1 mm spot size on device, capable of directly measuring undriven thermal motions of various devices at room temperature, with fm Hz À 1/2 -level displacement sensitivities (see Methods) 31 . In brief, thermodynamic fluctuations agitate a mechanical structure (as dictated by fluctuation-dissipation theorem and equipartition theorem) 32 such that each of the structure's eigenmodes emerges as a thermomechanical resonance in the frequency-domain noise spectrum, with a displacement noise spectral density of…”
Section: Resultsmentioning
confidence: 99%
“…We have engineered the system to achieve displacement sensitivities at pm Hz À 1/2 to fm Hz À 1/2 levels for devices in various materials and structures 31 , by further advancing the interferometry techniques developed during the last decade [53][54][55][56] . To experimentally determine the displacement sensitivity (resolution, or limit of detection for displacement), we first relate the amplitude of the thermomechanical motion to the measured noise level in the spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Q-factors from few tens to 10 4 have been reported in the literature for simple resonant nano and micromechanical systems. 9,28,[30][31][32] This makes In 2 O 3 microrods a very promising material for the fabrication of resonant micromechanical devices such as sensors. Besides, the combination of high quality optical resonances, as reported recently for these In 2 O 3 rods, 17 and the mechanical resonance properties reported here, could offer the possibility to increase their response through the optomechanical coupling, as reported for other systems by Vahala et al 4,5 This recent application field will require for a more accurate measurements of In 2 O 3 mechanical properties, as those reported here.…”
mentioning
confidence: 99%